2020
DOI: 10.1002/jnr.24766
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor dysfunction in a mild mouse model of cortical contusion injury without significant neuronal loss is associated with increases in inflammatory proteins with innate but not adaptive immune functions

Abstract: Traumatic brain injury is a leading cause of mortality and morbidity in the United States. Acute trauma to the brain triggers chronic secondary injury mechanisms that contribute to long-term neurological impairment. We have developed a single, unilateral contusion injury model of sensorimotor dysfunction in adult mice. By targeting a topographically defined neurological circuit with a mild impact, we are able to track sustained behavioral deficits in sensorimotor function in the absence of tissue cavitation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In our study, the outcome of PCV3 inoculation to CDCD piglets indicates PCV3 infection cannot induce obvious clinical symptoms and pathological changes. The appearance of clinical symptoms and the severity of the disease may be affected by the immune status of pigs [ 38 , 39 ], stress factors that cause systemic inflammation [ 40 , 41 ], or coinfection with other pig pathogens [ 42 , 43 ]. The cumulative results in our study demonstrated that PCV3 trend to low pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the outcome of PCV3 inoculation to CDCD piglets indicates PCV3 infection cannot induce obvious clinical symptoms and pathological changes. The appearance of clinical symptoms and the severity of the disease may be affected by the immune status of pigs [ 38 , 39 ], stress factors that cause systemic inflammation [ 40 , 41 ], or coinfection with other pig pathogens [ 42 , 43 ]. The cumulative results in our study demonstrated that PCV3 trend to low pathogenicity.…”
Section: Resultsmentioning
confidence: 99%